Linguoculturology as a new field of linguistics (Progress Annals: Journal of Progressive Research, 2024)
Every person is a part of national culture which includes national traditions, language, history and literature. Nowadays, the economic, cultural and scientific contacts between nations are becoming closer.The activation of culturological studies turned the spotlight on linguoculturology.This article explores different views about lingvoculturology and shows different methods of analysis. In addition to this, several directions of linguculturology are mentioned. The study aims to give a brief information about this branch of linguistics as it is very important in teaching English as a second language.